Correlation of heart rate and body weight with various electrocardiographic and echocardiographic parameters in indigenous breeds of dogs - S. Bhargavi; T.A. Kannan; Geetha Ramesh; D. Sumathi; A. Arun Prasad (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The current study was aimed to study the correlation of heart rate and body weight with various electrocardiographic and echocardiographic parameters in indigenous breeds of dogs of Tamil Nadu such as Rajapalayam and Chippiparai. The dogs are known for their skill, companionship and their adaptation to the country’s tropical climate. Study population consisted of 24 overtly healthy Rajapalayam (n=12) and Chippiparai (n=12) dogs, sighthound breeds of Tamil Nadu. After recording the relevant parameters, the values were correlated statistically and results obtained.